2021
DOI: 10.1038/s41598-021-89281-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural and physical properties of 99 complex bulk chalcogenides crystals using first-principles calculations

Abstract: Chalcogenide semiconductors and glasses have many applications in the civil and military fields, especially in relation to their electronic, optical and mechanical properties for energy conversion and in enviormental materials. However, they are much less systemically studied and their fundamental physical properties for a large class chalcogenide semiconductors are rather scattered and incomplete. Here, we present a detailed study using well defined first-principles calculations on the electronic structure, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…[1][2][3][4] The power conversion efficiency of Cu 2 ZnSnS 4 is relatively high (9%), but much remains to be done before it can rival conventional materials such as Si (420%). It has become very popular to suggest new photovoltaic materials through first-principles calculations and machine learning algorithms; 5,6 such prognostications are facile to make but hardly ever tested through experiment. Among various strategies to increase the efficiency, substitution of Zn in Cu 2 ZnSnS 4 with Cd and Hg has been proposed, [7][8][9][10][11][12] even though this entails new risks of toxicity that will eventually need to be mitigated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The power conversion efficiency of Cu 2 ZnSnS 4 is relatively high (9%), but much remains to be done before it can rival conventional materials such as Si (420%). It has become very popular to suggest new photovoltaic materials through first-principles calculations and machine learning algorithms; 5,6 such prognostications are facile to make but hardly ever tested through experiment. Among various strategies to increase the efficiency, substitution of Zn in Cu 2 ZnSnS 4 with Cd and Hg has been proposed, [7][8][9][10][11][12] even though this entails new risks of toxicity that will eventually need to be mitigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that C 11 and C 33 reflect the resistance to the deformation of the crystal along the [1 0 0] and [0 0 1] directions, respectively. 42,43 The results imply that there is a strong resistance to the compression along with the a ( C 11 ) or c ( C 33 ) axis. 44,45…”
Section: Resultsmentioning
confidence: 90%
“…reflect the resistance to the deformation of the crystal along the [1 0 0] and [0 0 1] directions, respectively. 42,43 The results imply that there is a strong resistance to the compression along with the a (C 11 ) or c (C 33 ) axis. 44,45 It is observed from To our knowledge, there is no experimental optical band gap for the compound AB 2 As 2 in the literature.…”
Section: Elastic Propertiesmentioning
confidence: 89%
“…As the chemical components of different phases are the same, we consider the average Pb−I bond length to explain the trend in the principal elastic constants (i.e., C 11 , C 22 , and C 33 ). C 11 , C 22 , and C 33 reflect the resistance to the deformation of the crystal along x, y, and z directions, 22,59 respectively. As shown in Figure 2b, for the cubic phase, the lattice constants of Thus, it can be found that for the cubic and tetragonal phases, the principal elastic constants of the crystal follow an opposite trend to their lattice constants.…”
Section: Methodsmentioning
confidence: 99%